Sustainability and Inflation: A Bi-front Malaise - Cossiga, Giovanni Antonio (Advances in Social Sciences Research Journal, 2023)
The singular presence together of inflation and deflation is only apparently improper because we must always distinguish on the subject of inflation, about which phenomenon we are talking. In general, we can say that the two phenomena - called classics - cannot share. With an important distinction. If inflation or deflation is - as already said "classical" - that is, it affects the economic system due to errors made by governments in managing the economy. In this case, inflation has its own characteristics: that is, it is subject to constant acceleration and its race continues until monetary policy intervenes with the rise in the interest rate. Different the case of inflation from international prices, due to the increase in the cost of energy and rare earths, as well as cereals, etc. Well in this case, the subjection of daily prices is linked to the evolution to which they are subject due to speculation and to the selfishness of producers. In the case of international price inflation, the decision of central banks to raise the cost of borrowing has a marginal effect on cost inflation. However, it has a strong indirect effect because the rising cost of credit puts lead into the pockets of speculators. With the result of containing the speculative thrust to the advantage of domestic prices which are slowing down. We are in a period of creeping deflation and tensions on the stock markets and capital assets front, two phenomena that have direct repercussions on daily spending and aggravate the difference between the rich and classes close to poverty. It is therefore essential to mitigate the social tensions that accumulate that the issue of international price controls, starting with wheat and energy, are addressed at the G7 and G20 level for a policy of moderation on these prices. On the topic of the recurring pressure of stock market values and of equity assets, in search of the reasons for the unjustified rise, we point out the hypothesis that this for the moment moody rise in values has the possibility that it could be a sort of hypothetical foretelling of human society when we have achieved full neutrality with nature. At the time, a sharp acceleration in development could change our economics of scarcity.